A mechanism coordinating root elongation, endodermal differentiation, redox homeostasis and stress response. (18th June 2021) - Fu, Jing; Zhang, Xinglin; Liu, Jiaming; Gao, Xudong; Bai, Juan; Hao, Yueling; Cui, Hongchang
SUMMARY: Root growth relies on both cell division and cell elongation, which occur in the meristem and elongation zones, respectively. SCARECROW ( SCR ) and SHORT‐ROOT ( SHR ) are GRAS family genes essential for root growth and radial patterning in the Arabidopsis root. Previous studies showed that SCR and SHR promote root growth by suppressing cytokinin response in the meristem, but there is evidence that SCR expressed beyond the meristem is also required for root growth. Here we report a previously unknown role for SCR in promoting cell elongation. Consistent with this, we found that the scr mutant accumulated a higher level of reactive oxygen species (ROS) in the elongation zone, which is probably due to decreased expression of peroxidase gene 3, which consumes hydrogen peroxide in a reaction leading to Casparian strip formation. When the oxidative stress response was blocked in the scr mutant by mutation in ABSCISIC ACID 2 ( ABA2 ) or when the redox status was ameliorated by the upbeat 1 ( upb1 ) mutant, the root became significantly longer, with longer cells and a larger and more mitotically active meristem. Remarkably, however, the stem cell and radial patterning defects in the double mutants still persisted. Since ROS and peroxidases are essential for endodermal differentiation, these results suggest that SCR plays a role in coordinating cell elongation, endodermal differentiation, redox homeostasis and oxidative stress response in the root. We also provide evidence that this role of SCR is independent of SHR, even though they function similarly in other aspects of root growth and development. Significance Statement: Root growth relies on both cell division and cell elongation, which occur in the meristem and elongation zones, respectively. Much is known about the mechanisms regulating meristematic activity, but it is unclear how cell elongation is modulated. This study reveals a previously unrecognized role for SCARECROW in cell elongation and a mechanism coordinating root growth, endodermal differentiation, redox homeostasis and the abiotic stress response.